Agro-Product Processing Technology: Principles and Practice - Bala, B K (CRC Press, 2020)
Global food security is a challenging issue to meet the food and nutritional requirements and has become an issue for national policymakers and public concern. There is a need to enhance agricultural production as well as to reduce the postharvest loss, improve the quality of the processed products and add value to the products to make more quality food available. Agro product processing technology plays the major role to reduce the post harvest losses, improve the quality of processed products and add value to the products. This also would generate employment and ultimately would contribute to food security.